2017
DOI: 10.1016/j.phpro.2017.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Staging of RF-accelerating Units in a MEMS-based Ion Accelerator

Abstract: Multiple Electrostatic Quadrupole Array Linear Accelerators (MEQALACs) provide an opportunity to realize compact radio-frequency (RF) accelerator structures that can deliver very high beam currents. MEQALACs have been previously realized with acceleration gap distances and beam aperture sizes of the order of centimeters. Through advances in Micro-Electro-Mechanical Systems (MEMS) fabrication, MEQALACs can now be scaled down to the sub-millimeter regime and batch processed on wafer substrates. In this paper we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…9A). Here, the accelerating wafers and Faraday cup were replaced by glass ESQAs and a scintillator (RP 400 plastic scintillator) together with a fast image intensifying camera (Princeton instruments) [9]. After mounting the ESQA, the positive and negative bias on the ESQA electrodes were swept to observe the focusing/defocusing effect.…”
Section: Experimental Setup For Ion Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…9A). Here, the accelerating wafers and Faraday cup were replaced by glass ESQAs and a scintillator (RP 400 plastic scintillator) together with a fast image intensifying camera (Princeton instruments) [9]. After mounting the ESQA, the positive and negative bias on the ESQA electrodes were swept to observe the focusing/defocusing effect.…”
Section: Experimental Setup For Ion Accelerationmentioning
confidence: 99%
“…Using this external resonator (voltage amplifier), an accelerator consisting of six accelerating gaps was demonstrated [9]. The external resonators will increase the size, power and cost of a complete accelerator system.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication we showed that a printed-circuit-board based (PCB) ESQA can be used to focus and accelerate argon ion beams [9,10]. However, the laser microfabrication and side-wall metal deposition processes are not suitable for mass fabrication.…”
Section: Figure 1: (A) 3d Schematic Of Multi-beam Accelerator With Io...mentioning
confidence: 99%